Proposal for a Standard Format for Neurophysiology Data Recording and Exchange. Issue 5 (October 2016) - Stead, Matt; Halford, Jonathan J.
Abstract : Summary: The lack of interoperability between information networks is a significant source of cost in health care. Standardized data formats decrease health care cost, improve quality of care, and facilitate biomedical research. There is no common standard digital format for storing clinical neurophysiologic data. This review proposes a new standard file format for neurophysiology data (the bulk of which is video-electroencephalographic data), entitled the Multiscale Electrophysiology Format, version 3 (MEF3), which is designed to address many of the shortcomings of existing formats. MEF3 provides functionality that addresses many of the limitations of current formats. The proposed improvements include (1) hierarchical file structure with improved organization; (2) greater extensibility for big data applications requiring a large number of channels, signal types, and parallel processing; (3) efficient and flexible lossy or lossless data compression; (4) industry standard multilayered data encryption and time obfuscation that permits sharing of human data without the need for deidentification procedures; (5) resistance to file corruption; (6) facilitation of online and offline review and analysis; and (7) provision of full open source documentation. At this time, there is no other neurophysiology format that supports all of these features. MEF3 is currently gaining industry and academic community support. The authors propose the use of the MEF3 as a standard format for neurophysiology recording and data exchange. Collaboration between industry, professional organizations, research communities, and independent standards organizations is needed to move the project forward.